SIBLING RIVALRY : GAMBARAN DINAMIKA PENGETAHUAN, SIKAP DAN REAKSI IBU - Yuditia Prameswari; Ika Novita Sari (Ensiklopedia of Journal, 2019)
Sibling Rivalry is an event of tension and conflict between siblings who seeking for parents affection, which is often characterized by disputes and jealousy in fighting over time, seeking for attention and love from their parents. The aspects of Sibling Rivalry are aggressive behavior, crying, anger (protesting), spoiled and fussy. Mother's knowledge is very important in dealing with problems in children and must provide a lot of time and energy to reorganize relationships with their children. This is descriptive study to get pictures of the dynamics of knowledge, attitudes and reactions of mothers towards the behavior of children suspected of experiencing feelings of Sibling Rivalry. Researchers had conducted a preliminary study in the form of observations and interviews based on the complaints of mothers that their children had a difficult time. Some of them can solve and understand the problems that occur, but some other mothers feel they do not have an understanding of the situation at hand. The questionnaire was also given to the mother to give a check list on the behavior suspected to be sibling rivalry. As a result, as many as 48 mothers gave an alleged response to sibling rivalry. This study uses a quantitative descriptive type, taken by the total sampling method to the mothers whose children attend the Play Group and TK Cookies Kids Batam as many as 50 people. Methods of collecting data with questionnaires, observation and interviews, and Chi Square data analysis. The results of the study were 38 mothers who had good knowledge and positive reactions to the occurrence of Sibling Rivalry and 12 mothers had sufficient knowledge and reaction to the occurrence of Sibling Rivalry